Ang paglinang ng Eucheuma. (Eucheuma farming). - Trono Jr., Gavino C. (Seaweeds Information Center, UPMSI, 1989)
Pag-uma sa guso = eucheuma farming translated in Cebuano by Ms. Teresita Buchan-Antalan